Using IT2FS, DEMATEL, and TOPSIS to Build Sustainable Solutions for Vietnamese Coffee - Nguyen, Hoang Phuong; Bui, Thuy Chi; Nguyen, Mai Hoang Dieu; Trang Bui, Dang Thien; Nguyen, Thi Quynh Nhu; Nguyen, Hoang Truc Khanh; Le, Thanh Tam; Nguyen, Thi Lieu; Bui, Viet Duc (Society of Visual Informatics, 2025)
Ensuring the sustainability of coffee supply chains in emerging economies is a growing concern due to complex systemic barriers and limited strategic direction. The Vietnamese coffee industry is ranked second in global coffee exports and plays a vital role in Vietnam's economy. The Vietnamese coffee supply chain encompasses a vast network of smallholder farmers, local processors, and exporters, presenting challenges related to sustainability, price volatility, and quality control. This study proposes the use of Interval Type-2 Fuzzy Sets (IT2FS), Decision-Making Trial and Evaluation Laboratory (DEMATEL), and the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) to analyze and rank the barriers and strategic interventions in Vietnam's coffee sector. Using IT2FS-DEMATEL, we looked at the driving and dependent relationships between six main barriers and six solutions that focus on sustainability. The results showed that the DEMATEL-based structural analysis revealed that Unstable Market and Trade Conditions had the most substantial driving influence. At the same time, the Lack of Best Cultivation Quality Standards was the most dependent factor. The TOPSIS analysis ranked Establishing National Coffee Cultivation Standards as the top solution, which was remarkably close to the optimal solution vector. These results provide a thorough, evidence-based plan for determining the initial actions to take in stabilizing Vietnam's coffee supply chain during times of volatility. It gives policymakers and industry stakeholders a clear framework for developing targeted actions to enhance the sustainability and resilience of coffee supply chains.